Laser-assisted thermal imprinting of glass guided mode resonant (GMR) optical filter - Lee, Helen May Shian; Syarifah Nur Hasanah, Syed Kamarudin; Ismayuzri, Ishak; Ahmad Shahir, Jamaludin; Ahmad Rosli, Abdul Manaf; Mohd Zairulnizam, Mohd Zawawi (Penerbit UMP, 2021)
Laser-assisted thermal imprinting of glass nanostructures is demonstrated. Compare to the existing thermal imprinting, this method significantly reduced the contact imprinting time. The quality of the replicated glass nanostructures revealed by field emission scanning electron microscope ( SEM) and atomic force microscope ( AFM) exhibited a very smooth surface finish that closely matched the profile of the silicon mold. As proof-of-concept, the utility of laser-assisted, imprinted glass nanostructures as guided-mode resonant (GMR ) optical filter was evaluated. The peak spectral values obtained were satisfactory; which yielded an average FWHM and PWV of 4.6 nm and 691.39 nm respectively.